Implementasi Kriptografi Pengamanan Data Pribadi Siswa SMA Swasta Jaya Krama Beringin Dengan Algoritma RC4 - Rinaldi Maulana; R. Mahdalena Simanjorang (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
The personal data of the Jaya Krama Beringin Private High School students is required in the administrative data collection by the school. Personal data includes student identification such as student name, family identification number (NIK), gender, address, mobile number, e-mail, and so on. In today's digital era data is everything, with the development of the internet network that is increasingly easy to access, it is necessary to know and be aware of what things are personal data and what should be done to protect personal data. The research problem is that the personal data security of Jaya Krama Beringin High School students needs attention due to the widespread occurrence of data theft by hackers to be misused, it is necessary to need computer software for data security. The first step in the RC4 algorithm stage is to carry out the KSA (Key Scheduling Algorithm) process which at this stage is the process of forming an S-Box (Array S) with a length of 256 bytes (index 0 to 255) based on the encryption key. After using the XOR operation on the ciphertext with the key, the XOR result of the binary number obtained is converted into plaintext.